Enhanced methanation assisted by CO2 adsorption on a bimetallic catalytic fixed bed reactor - Mercader Plou, Víctor Daniel; Sanz Monreal, Pablo; Durán, Paul; Aragüés Aldea, Pablo; Francés, Eva; Herguido Hüerta, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2023)
This work studies the influence of introducing a CO2 adsorbent in a bimetallic catalytic fixed bed reactor. The catalyst is a lab-made Fe-Ni allow (2.5:7.5 wt/wt) supported on gamma alumina. Two CO2 adsorbents were tested in this study, lab made CaO and Na2O (10 wt/wt) supported on gamma alumina.